Ethnocultural images of everyday life in the prose of modern Eurasian writers - Bekmuratova, Aigerim E.; Khudaiberdina, Dinara A. (The New Research of Tuva, 2025)
The article analyzes ethnocultural imagery in the prose of contemporary writers who came of age in the Central Asian republics (Kyrgyzstan, Uzbekistan, Kazakhstan) at the turn of the 20th and 21st centuries. It substantiates the appropriateness of using the terms “Eurasian” and/or “Russophone” in reference to writers previously categorized by scholars as “Russian-language”— a designation that referred to bilingual authors who chose Russian as the language of their creative work, while not being ethnically Russian. The synthesis of the Russian linguistic system with a non-Russian system of imagery has given rise to a distinct literary tradition that cannot be unequivocally identified either with Russian literature or with any other national literature. This body of work constitutes a unique stratum of literature created by individuals possessing a non-singular, polychromatic worldview and, frequently, a hybrid or multiple ethnic identity.The primary materials for this study are works written in Russian by Sukhbat Aflatuni, Vadim Muratkhanov, Sandzhar Yanashev, Shevket Keshfidinov, Alexander Grishchenko, and Ilya Odegov, whose prose, while rendered in Russian, conveys a non-Russian system of imagery.It is demonstrated that, unlike the preceding generation of Soviet authors —ethnically non-Russian but writing in Russian — the prose of these contemporary writers is marked by an introverted poetics of imagery. Their heightened sense of self-identification and self-reflection is shown to be conditioned by the socio-political transformations associated with the dissolution of the USSR and the accompanying existential demands. The analysis focuses on ethnocultural images of everyday life: ritual practices (circumcision), elements of so-called sympathetic magic, belief in metamorphism (transformation), artifacts imbued with metaphysical significance (protective talismans, amulets), and spaces such as the bazaar and the museum, as well as a gastronomic artifact — the flatbread. The study notes convergences in anthropological tendencies and existential concerns as reflected in the artistic imagery of the selected authors. It reveals that the poetics of ethnocultural imagery in their works expresses a mythology of everyday life, endowed with existential functions — without the comprehension and representation of which the formation of a new historical memory becomes impossible.
Keywords: Eurasian; mythology of everyday life; artifact; ethnocultural image; national image; transculturation; ritual and ceremonial life; circumcision; bazaar; museum